The Purpose of Researching Amyotrophic Lateral Sclerosis - Hou, Rui (Transactions on Environment, Energy and Earth Sciences, 2024)
The neurological system is affected by a disease called amyotrophic lateral sclerosis that affects nerve cells in the brain and spinal cord. This paper examines several facets of the disease’s presentation characteristics, alterations in the illness, and contributing variables and therapeutic approaches. Speech slurring, difficulty swallowing, and arm or leg twitching and paralysis are common initial symptoms of amyotrophic lateral sclerosis. ALS gradually weakens the capacity to control the muscles involved in breathing, eating, speaking, and moving. The brain’s capacity to start and regulate voluntary motions is lost. The muscles eventually become non-functional, twitch (a condition known as fasciculations), and atrophy (the loss of muscle mass). This sickness will be caused by a multitude of elements, such as age, gender, and certain genetic information. Additionally, topics like the signs and symptoms of ALS and the possible "treatments" for the illness are covered. There is essentially no chance of a cure for this deadly illness. The symptoms worsen with time because the condition is progressive. That does not, however, imply that individuals should give up looking for a remedy.